1995
DOI: 10.1002/j.1460-2075.1995.tb00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Cadaverine induces closing of E. coli porins.

Abstract: We have used the electrophysiological technique of patch‐clamp to study the modulation of Escherichia coli porins by cadaverine. Porin channels typically have a very high probability to be open, and were not known to be inhibited by specific compounds until the present study. Experiments performed on patches of outer membrane reconstituted in liposomes reveal that cadaverine applied to the periplasmic side increases the frequency of channel closures in a concentration‐dependent fashion, and thereby decreases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
61
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 48 publications
7
61
0
1
Order By: Relevance
“…These results suggested that polyamines may modulate ion channel activities through direct binding to the channel proteins. This view is consistent with previous findings carried out in both animal and bacterial cells (Delavega and Delcour, 1995;Johnson, 1996). It has been reported that several specific polyamine-binding proteins in plasma membranes from plant cells were well characterized (Tassoni et al, 1998(Tassoni et al, , 2002.…”
Section: Discussionsupporting
confidence: 82%
“…These results suggested that polyamines may modulate ion channel activities through direct binding to the channel proteins. This view is consistent with previous findings carried out in both animal and bacterial cells (Delavega and Delcour, 1995;Johnson, 1996). It has been reported that several specific polyamine-binding proteins in plasma membranes from plant cells were well characterized (Tassoni et al, 1998(Tassoni et al, , 2002.…”
Section: Discussionsupporting
confidence: 82%
“…However, the regulation of porin function by potentially physiologically relevant factors is still poorly understood. We showed recently that polyamines inhibit chemotaxis and flux of ␤-lactam antibiotics through porins and thus decrease the permeability of the outer membrane (17). In electrophysiological experiments, we also demonstrated that cadaverine induces closures of porins (18).…”
mentioning
confidence: 81%
“…In particular, low pH leads to channel closure in the case of OmpF, OmpC, and PhoE (14 -17) and in a shift of the voltage dependence (18). Low pH may also be involved in cadaverine-mediated channel block (19). Atomic force microscopy of OmpF at low pH suggests that a conformation change of the loops exposed to the external surface is the reason for channel closure at low pH (20).…”
mentioning
confidence: 99%